Nonlinear Control - Zhou Gaofeng; Zhang Qi (Modern Control Systems: Theory, Design and Applications, 2025)
This chapter focused on the topic of nonlinear control for nonlinear systems that behave naturally. A linear system was only a simplification and approximation for our life. A nonlinear system was perhaps the nature of the society. In this chapter, relative methods (such as describing function, Popov analysis, phase-plane analysis method and so on) of nonlinear systems were provided to analyze and design a nonlinear system. Furthermore, stability and controllability analysis of nonlinear systems were introduced to help readers analyze and design a nonlinear system. Besides these contents, the inverse system method was also explored and explained for readers to further comprehend nonlinear systems for feedback control design.